Role of perivascular and meningeal macrophages in outcome following experimental subarachnoid hemorrhage. Issue 8 (August 2021) - Wan, Hoyee; Brathwaite, Shakira; Ai, Jinglu; Hynynen, Kullervo; Macdonald, R Loch
The distribution and clearance of erythrocytes after subarachnoid hemorrhage (SAH) is poorly understood. We aimed to characterize the distribution of erythrocytes after SAH and the cells involved in their clearance. To visualize erythrocyte distribution, we injected fluorescently-labelled erythrocytes into the prechiasmatic cistern of mice. 10 minutes after injection, we found labelled erythrocytes in the subarachnoid space and ventricular system, and also in the perivascular spaces surrounding large penetrating arterioles. 2 and 5 days after SAH, fluorescence was confined within leptomeningeal and perivascular cells. We identified the perivascular cells as perivascular macrophages based on their morphology, location, Iba-1 immunoreactivity and preferential uptake of FITC-dextran. We subsequently depleted meningeal and perivascular macrophages 2 days before or 3 hours after SAH with clodronate liposomes. At day 5 after SAH, we found increased blood deposition in mice treated prior to SAH, but not those treated after. Treatment post-SAH improved neurological scoring, reduced neuronal cell death and perivascular inflammation, whereas pre-treatment only reduced perivascular inflammation. Our data indicate that after SAH, erythrocytes are distributed throughout the subarachnoid space extending into the perivascular spaces of parenchymal arterioles. Furthermore, meningeal and perivascular macrophages are involved in erythrocyte uptake and play an important role in outcome after SAH.